Learning Strategies Used Actual Teacher Morals of MTsN Binjai Students (Observation of Student Learning in MTs) - Devi Indah Sari (Britain International for Academic Research (BIAR) Publisher, 2022)
In this regard, the strategy conveys learning so that learning becomes effective and efficient and becomes easier to understand. Akidah learning in Madrasas is one of the PAI subjects that emphasizes the ability to believe, understand and maintain the right faith and live and practice good values. Thus, aqidah learning materials not only teach knowledge about religion, but also shape students' personalities so that they have strong faith and piety. So, the purpose of this observation or mini research is to find out how the teacher's strategy in teaching moral aqidah subjects is which we all know that moral aqidah subjects are very important to be taught, especially in this current era. To find out, the researchers used qualitative research methods in the form of interviewing objects (teachers) directly. And the results obtained are in teaching the learning of the teacher's morals using the CBSA strategy (active student learning method) which is very effective according to the teacher or object to be used in teaching.